Comparison of Capsule Endoscopy Findings to Subsequent Double Balloon Enteroscopy: A Dual Center Experience. (1st September 2015) - Kalra, Amandeep S.; Walker, Andrew J.; Benson, Mark E.; Soni, Anurag; Guda, Nalini M.; Misha, Mehak; Gopal, Deepak V.
Abstract : Background . There has been a growing use of both capsule endoscopy (CE) and double balloon enteroscopy (DBE) to diagnose and treat patients with obscure gastrointestinal blood loss and suspected small bowel pathology. Aim . To compare and correlate sequential CE and DBE findings in a large series of patients at two tertiary level hospitals in Wisconsin. Methods . An IRB approved retrospective study of patients who underwent sequential CE and DBE, at two separate tertiary care academic centers from May 2007 to December 2011, was performed. Results . 116 patients were included in the study. The mean age ± SD was 66.6 ± 13.2 years. There were 56% males and 43.9% females. Measure of agreement between prior capsule and DBE findings was performed using kappa statistics, which gave kappa value of 0.396 withP < 0.001 . Also contingency coefficient was calculated and was found to be 0.732 (P < 0.001 ). Conclusions . Our study showed good overall agreement between DBE and CE. Findings of angioectasia had maximum agreement of 69%.